2021
DOI: 10.24215/18539912e128
|View full text |Cite
|
Sign up to set email alerts
|

Adaptación del Information Competency Assessment Instrument y su aplicación a estudiantes de pregrado de las universidades de Magallanes y Playa Ancha

Abstract: Este artículo analiza la adaptación, aplicación, comportamiento y análisis de cualidades psicométricas del instrumento Information Competency Assessment Instrument (ICAI), desarrollado por Rodney Marshall de la Eastern Illinois University (2006), a través de la aplicación sobre una muestra estratificada de estudiantes (n= 381) de los niveles superiores de la Universidad de Playa Ancha y la Universidad de Magallanes. Debido a la baja consistencia interna del instrumento original, se desarrolló un análisis facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 22 publications
0
1
0
1
Order By: Relevance
“…Several studies have used this instrument to assess the IL competencies of students and have affirmed the validity of the instrument (Valenzuela et al , 2019; Larsen et al , 2010; Cantwell, 2010; Ferguson et al , 2006). A recent study by Urra et al (2021) used this instrument to measure IL competencies and concluded that the instrument is reliable, as the results from their study show “adequate levels of reliability” (p. 128). Moreover, Marshall (2006) used the instrument in two different studies and indicated that “with the Cronbach Alpha being in the high eighties and low nineties each time it is given shows consistent reliability” (p. 18).…”
Section: Methodsmentioning
confidence: 99%
“…Several studies have used this instrument to assess the IL competencies of students and have affirmed the validity of the instrument (Valenzuela et al , 2019; Larsen et al , 2010; Cantwell, 2010; Ferguson et al , 2006). A recent study by Urra et al (2021) used this instrument to measure IL competencies and concluded that the instrument is reliable, as the results from their study show “adequate levels of reliability” (p. 128). Moreover, Marshall (2006) used the instrument in two different studies and indicated that “with the Cronbach Alpha being in the high eighties and low nineties each time it is given shows consistent reliability” (p. 18).…”
Section: Methodsmentioning
confidence: 99%
“…Esta dimensión, según Valenzuela et al (2021), consiste en analizar las fuentes de forma crítica, y seleccionar la información que brinde veracidad y sustento. Por ello, se deben considerar cuestiones éticas que suponen el uso de la información con propósitos legales.…”
Section: Evaluación De La Informaciónunclassified